Study on nutrient supply in relation to feeding system of buffalo in Chitwan, Nepal - Shah, Manoj Kumar; Tabata, Yusuke; Kumagai, Hajime; Hayashi, Yoshiaki (Journal of Agriculture and Natural Resources, 2018)
Livestock farming in Nepal, especially buffalo farming alone contributes a major share in livelihoods of farmers. Stall feeding of buffalo is common in Chitwan with occasional grazing. This raises questions about status of nutrients supplied to maintain productivity as feed resources varied in forest and crop land according to the season. A study was carried out in Chitwan from April 2015 to March 2016 to find out the status of nutrient supply in relation to the feeding system of buffalo. Total fifteen farms were selected from three villages, the amount of feedstuff fed to the animals was measured every month and the nutrient contents of the feed were analyzed. The mean concentrations of DM, CP, TDN, Ca and P were 641g/kg, 75.0 g/kg, 462 g/kg, 4.9 g/kg and 4.2 g/kg. A significant difference of CP contents among the villages was observed (72.0 g/kg, 70.7 g/kg and 81.2 g/kg (P